Enantioselective Synthesis of α-Hydroxyamino Ketones by a Chiral Phosphine–Silver Complex Catalyzed N-Nitroso Aldol Reaction - Yanagisawa, Akira; Kasahara, Shiho; Takeishi, Akihiro; Marui, Tomoki (Synlett, 2022)
A catalytic asymmetric N-nitroso aldol reaction of alkenyl trifluoroacetates with nitrosoarenes was achieved using a DTBM-SEGPHOS·AgOTf complex as the chiral precatalyst and KHMDS as the base precatalyst in the presence of methanol. Optically active α-hydroxyamino ketones with up to 89% ee were regioselectively obtained in moderate to high yields not only from acyclic alkenyl esters but also from cyclic ones through the in situ generated chiral silver enolates.
Keywords: asymmetric catalysis; alkenyl ester; nitroso aldol reaction; nitrosoarene; silver